The U.S. Supreme Court a very short introduction - Greenhouse, Linda (New York : Oxford University Press, 2012)
For 30 years, Linda Greenhouse chronicled the activities of the justices as the Supreme Court correspondent for the New York Times. In this concise volume, she draws on her deep knowledge of the court's history as well as of its written and unwritten rules to show the reader how the Supreme Court really works.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: United States. -- Supreme Court; Judicial process -- United States; Law; Laws of specific jurisdictions & specific areas of law